Balancing assessment of depth and breadth in the dental curriculum: A bi-dimensional assessment strategy - Srinivas Sulugodu Ramachandra; Sylvia Western J; Khairiyah Abdul Muttalib (Elsevier, 2020)
Introduction: Integrated curricula are being increasingly adopted in health professions, owing to their advantages including patient-centred training and development of critical thinking. Similarly, the majority of dental Universities have either moved away from discipline-specific towards integrated curricula or have incorporated elements of integration. Despite several advantages offered by the integrated curriculum, one disadvantage is failure to assess depth of knowledge. Assessing the depth of knowledge is a characteristic of discipline-specific curriculum. This commentary describes the inclusion of both discipline-based and integrated assessments at Faculty of Dentistry, SEGi University, Malaysia. Material and methods: Module tests (discipline-based assessments) comprising of discipline specific questions are conducted at the end of every term, mimicking the traditional discipline-specific assessment. Questions in the module tests are intended to assess the depth of knowledge of students. Mid semester examinations are conducted at the end of the semester, mimicking the integrated assessment. Integrated questions are intended to test the breadth of knowledge of students. Results: Lecturers and students felt introduction of module tests, helped them to prepare for topics in a phased manner and better answer questions posed by lecturers during case discussions and clinical presentations. The 'borderline distinction' students felt that studying for module tests provided them with the depth of knowledge essential to answer questions during viva voce. Discussion: Including both the traditional and integrated methods of assessments would engage students in a learning experience developing their breadth and depth of knowledge. Further prospective research is essential to assess the impact of this assessment strategy.